Enhancing the Efficiency of Polariton OLEDs in and Beyond the Single-Excitation Subspace - Siltanen, Olli; Luoma, Kimmo; Musser, Andrew J.; Daskalakis, Konstantinos S. (WILEY-V C H VERLAG GMBH, 2025)
Organic light-emitting diodes (OLEDs) have redefined lighting with their environment-friendliness and flexibility. However, only 25% of the electronic states of organic molecules can emit light upon electrical excitation, limiting the overall efficiency of OLEDs. Strong light-matter coupling, achieved by confining light within OLEDs using mirrors, creates hybrid light-matter states known as polaritons, which could "activate" the remaining 75% electronic triplet states. Here, triplet-to-polariton transition is studied and rates for both reverse inter-system crossing and triplet-triplet annihilation are derived. In addition, how the harmful singlet-singlet annihilation could be reduced with strong coupling is explored.